log(6)36=2x+4

Simple and best practice solution for log(6)36=2x+4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for log(6)36=2x+4 equation:


Simplifying
log(6) * 36 = 2x + 4

Reorder the terms for easier multiplication:
6 * 36glo = 2x + 4

Multiply 6 * 36
216glo = 2x + 4

Reorder the terms:
216glo = 4 + 2x

Solving
216glo = 4 + 2x

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Divide each side by '216lo'.
g = 0.01851851852l-1o-1 + 0.009259259259l-1o-1x

Simplifying
g = 0.01851851852l-1o-1 + 0.009259259259l-1o-1x

See similar equations:

| 2x^2+4-1=0 | | 35x+25-12x+60=80 | | 5.49x+1=30.1401+x | | 9x^2-1=24 | | 4n+3+8=7 | | 3x-6x^2= | | 3025=1.3*3.14*r^3 | | 15+3x=500 | | (x)3x+1=30 | | 5.52x+16.56=33.12 | | 2600=2*3.14*r^2+2*3.14*r*37 | | 2x(2+4x+2t)= | | -114=6-6x | | -x+.25=.45 | | 193.0472=2*3.14*r^2+2*3.14*r*7.7 | | 3x^2-3x^3-12x+12=0 | | 22=-x+8 | | 2x(2+4x)= | | -3[4x-2+5(x+1)]=-5x-4 | | 6c-9c^2= | | 6-6x+6=4x-8 | | 2x+4+2=48 | | 3(g-1)= | | X^2(x+2)-x(x+2)-6(x+2)= | | 0=4x^4-29x^2+7 | | 5h+3=2h-9 | | p(x)=4x^4-29x^2+7 | | X^4-17x^2+16= | | 2x^2+1x=21 | | 950.6664=4*3.14*r^2 | | 5y=135+9x | | 2x+7=2(3x-5) |

Equations solver categories